El cuidado de la salud mental: un reto para garantizar entornos de trabajo seguros y saludables - Quiñones Infante, Sergio (Pontificia Universidad Católica del Perú, 2024)
This paper is aimed to analyze the strong link that exists between the implementation of appropriate measures to care for the mental health of workers in the workplace and the effective compliance by employers with guaranteeing a safe and healthy environment in all work centers. With this purpose, we begin by developing the applicable theoretical framework within which the concept of “mental health at work” is framed; subsequently, we analyze data about the current state of this public problem, both at a global and national level, placing particular emphasis on those investigations that show the negative impact that inadequate mental health care generates on the work productivity of workers. Finally, we will evaluate the current and future challenges that mental health care at work presents from the perspective of public policies and from the perspective of business organizations.

El objeto del presente artículo es analizar la íntima vinculación que existe entre la implementación de medidas adecuadas para el cuidado de la salud mental de las y los trabajadores en el ámbito laboral y el efectivo cumplimiento por parte de los empleadores de garantizar un entorno seguro y saludable en todos los centros de trabajo. A tal efecto, empezamos desarrollando el marco teórico aplicable dentro del cual se encuadra el concepto de “salud mental en el trabajo”; posteriormente analizamos data acerca del estado actual de este problema público, tanto a nivel global como nacional, haciendo particular incidencia en aquellas investigaciones que evidencian el impacto negativo que genera un inadecuado cuidado de la salud mental en la productividad laboral de las y los trabajadores. Finalmente evaluaremos los retos actuales y futuros que el cuidado de la salud mental en el trabajo presenta desde el enfoque de las políticas públicas y desde la mirada de las organizaciones empresariales.
Mental health care: a challenge to guarantee safe and healthy work environments
Keywords: Mental health; Work; Productivity; Safe and healthy environments; WHO; ILO; Salud mental; Trabajo; Productividad; Entornos seguros y saludables; OMS; OIT; https://purl.org/pe-repo/ocde/ford#5.05.00